Rhinergasilus unguilongus n. sp. (Copepoda: Ergasilidae): A Gill Parasite of the Freshwater Fish Prochilodus lineatus (Valenciennes, 1837) (Actinopterygii: Prochilodontidae) from the Neotropical Region, Brazil - Narciso, Rodrigo Bravin [UNESP]; Perbiche-Neves, Gilmar; da Silva, Reinaldo José [UNESP] (Springer Nature, 2020)
Purpose: To describe, based on morphological features, a new copepod species of Rhinergasilus, Rhinergasilus unguilongus n. sp., collected from gills of the Streaked prochilod, Prochilodus lineatus (Valenciennes, 1837), sampled in the Veados and Paranapanema Rivers, two tributaries of the Jurumirim Reservoir (Upper Paranapanema River, Paraná River Basin), São Paulo State, Brazil. Methods: Fish were collected using multi-panel gill nets. The gills of each fish were washed and examined for copepods using a stereo microscope. The copepods found were stored in 70% ethanol, cleared in lactic acid, and mounted in Hoyer’s medium. Drawings were made with the aid of a microscope equipped with a drawing tube. Results: The new copepod species can be distinguished from its two congeners, Rhinergasilus piranhus (type-species) Boeger et Thatcher, 1988 and Rhinergasilus digitus Narciso, Brandão, Perbiche-Neves et Silva, 2020, due to its extremely long antennary claw (etymology of the species), being longer than the other antennary segments; third leg lacking any interpodal plate; and third endopodal segment of third leg lacking a distal spine. Conclusions: Based on the morphological differences, we erected a new species of Rhinergasilus. The new copepod represents the second report of a Rhinergasilus species parasitizing a fish from the Jurumirim Reservoir. It also represents the first report of this genus in P. lineatus.
Keywords: Crustacea; Cyclopoida; Ectoparasite; Paranapanema; Ribeirão dos veados; Streaked prochilod